Spatial Statistics for Dyadic Data: Analyzing the Relationship Landscape. - Wood, Nathan D.; Okhotnikov, Ilya A. (Journal of Marital & Family Therapy, 2017)
Spatial statistics has a rich tradition in earth, economic, and epidemiological sciences and has potential to affect the study of couples as well. When applied to couple data, spatial statistics can model within- and between-couple differences with results that are readily accessible for researchers and clinicians. This article offers a primer in using spatial statistics as a methodological tool for analyzing dyadic data. The article will introduce spatial approaches, review data structure required for spatial analysis, available software, and examples of data output.